2011
DOI: 10.1111/j.1525-139x.2011.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Pruritic Rash and Eosinophilia in a Patient Receiving Peritoneal Dialysis

Abstract: A 28-year-old woman with end-stage renal disease maintained on peritoneal dialysis developed a hyperpigmented macular pruritic rash on multiple parts of her body associated with an eosinophilia of 22%. The consulting allergist suspected a silicone allergy from the peritoneal dialysis catheter. A patch test confirmed this diagnosis. Treatment with both topical and systemic steroids was ineffective. Following a living nonrelated renal transplant and removal of the catheter the rash and eosinophilia resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…To the Editor, In response to the letter by Paal Klykken, Ph.D., and Jim Curtis regarding the case report by Patel et al (1), entitled Pruritic Rash and Eosinophilia in a Patient Receiving Peritoneal dialysis, we agree with some of the assertions of Klykken and Curtis. They stated that three independent review panels investigated (as a result of the breast implant debate) the issue of silicone immunogenicity and ''concluded that there is no convincing evidence to support, or lend biologic plausibility to an association of silicone breast implants with immune related human health conditions.''…”
Section: This Letter Was Referred To the Authors Of The Article In Qusupporting
confidence: 81%
“…To the Editor, In response to the letter by Paal Klykken, Ph.D., and Jim Curtis regarding the case report by Patel et al (1), entitled Pruritic Rash and Eosinophilia in a Patient Receiving Peritoneal dialysis, we agree with some of the assertions of Klykken and Curtis. They stated that three independent review panels investigated (as a result of the breast implant debate) the issue of silicone immunogenicity and ''concluded that there is no convincing evidence to support, or lend biologic plausibility to an association of silicone breast implants with immune related human health conditions.''…”
Section: This Letter Was Referred To the Authors Of The Article In Qusupporting
confidence: 81%
“…One case each of contact dermatitis and systemic allergic dermatitis was diagnosed by skin patch tests for peritoneal catheters, but histological information about skin patch test reactions was not provided. 1,2 Our case presented with a subcutaneous granulomatous reaction with eosinophil infiltration, but with no epidermal spongiosis observed typically in contact dermatitis. We therefore diagnosed our case as possible allergic granulomatous reaction to the Tenckhoff catheter.…”
Section: Discussionmentioning
confidence: 77%
“…A few reports have described cutaneous allergic reactions to peritoneal dialysis catheters during continuous ambulatory peritoneal dialysis (CAPD) . Here, we report a rare case of subcutaneous granulomatous reaction with eosinophil infiltration caused by a peritoneal dialysis catheter, and confirmed by skin tests.…”
mentioning
confidence: 65%
“…However, the presence of skin rash and erythema without drainage at the PD catheter exit site can be also due to early infection, allergic reaction to PD catheter material, 9 or to mechanical trauma. 4 Additionally, allergic reactions to PD catheter exit site care products such as antibiotic preparations (mupirocin and polysporin) 10 and antiseptic agents 11 , 12 can manifest as skin rash around PD catheter exit site.…”
Section: Discussionmentioning
confidence: 99%